Biotechnologies to tackle the challenge of neoantigen identification. (October 2020) - Arnaud, Marion; Duchamp, Margaux; Bobisse, Sara; Renaud, Philippe; Coukos, George; Harari, Alexandre
Graphical abstract: Highlights: Neoantigens represent promising targets for cancer immunotherapy. Interrogation of neoantigen-specific T cell responses is challenging. High-throughput strategies for immunogenicity validation are required. Bioengineering has and will continue to foster neoantigen identification. Abstract : Among immune correlates of clinical responses, tumor-specific neoantigens took the spotlight as relevant targets for cancer immunotherapy. The implementation of pipelines for personalized cancer therapy remains challenging due to the privacy, that is patient-specificity, of neoantigens and the low-frequency of neoantigen-specific T cells in blood and tumor samples. To overcome these obstacles, recent developments in the field of biotechnology have allowed the multiplexed identification of neoepitope-specific T cells. This review addresses the pros and cons of conventional neoantigen screening methodologies and highlights the current as well as the prospective biotechnological opportunities in the field.